1995
DOI: 10.1016/s0006-3495(95)80391-7
|View full text |Cite
|
Sign up to set email alerts
|

Radial packing, order, and disorder in collagen fibrils

Abstract: Collagen fibrils resemble smectic, liquid crystals in being highly ordered axially but relatively disordered laterally. In some connective tissues, x-ray diffraction reveals three-dimensional crystallinity in the molecular packing within fibrils, although the continued presence of diffuse scatter indicates significant underlying disorder. In addition, several observations from electron microscopy suggest that the molecular packing is organized concentrically about the fibril core. In the present work, theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
218
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(240 citation statements)
references
References 24 publications
13
218
0
3
Order By: Relevance
“…The next simplest distribution was a constrained bimodal distribution, in which prior knowledge of fibril arrangement in collagen was explicitly incorporated. The inhomogeneity of the fibril distribution has been suggested in previous studies using an atomic force microscope, where collagen fibrils with different packing densities were observed in the fiber bundle (58,59). Fibrous collagen domains of opposite orientation were observed in the tail tendon by Han et al (60).…”
Section: Discussion Of the Triple-helix Distribution With Respect To mentioning
confidence: 81%
See 1 more Smart Citation
“…The next simplest distribution was a constrained bimodal distribution, in which prior knowledge of fibril arrangement in collagen was explicitly incorporated. The inhomogeneity of the fibril distribution has been suggested in previous studies using an atomic force microscope, where collagen fibrils with different packing densities were observed in the fiber bundle (58,59). Fibrous collagen domains of opposite orientation were observed in the tail tendon by Han et al (60).…”
Section: Discussion Of the Triple-helix Distribution With Respect To mentioning
confidence: 81%
“…From previous measurements performed using SEM, NMR, and electron tomography, the most probable helix tilt angle was reported to be~17 . From the fiber diffraction studies, collagenous material was observed to be comprised of both a well-ordered fraction and a relatively disordered fraction (59). If it is reasonably assumed that the less-ordered fraction exhibits a broad distribution in orientations (corresponding to an effective c ð2Þ l;zzz =c ð2Þ l;zxx ¼ 3), the net distribution can be modeled as a sum of a normal distribution centered about zero with a mode at 17 and a broadly distributed antiparallel component.…”
Section: Discussion Of the Triple-helix Distribution With Respect To mentioning
confidence: 99%
“…The equilibration of the hydrated (wet) collagen microfibril (Fig. 3c) leads to a density of ≈1.19 g/cm 3 , a value that is halfway between the density of water and the density of dehydrated (dry) collagen, which has been estimated at 1.34 g/cm 3 [49]. A Ramachandran analysis of the solvated system (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Since pioneering experimental works by Fraser, Hulmes, Hess, Orgel, Fratzl and others it is known that virtually all collagen-based tissues are organized into hierarchical structures, where the lowest hierarchical level consists of triple helical collagen molecules (Fig. 1) [2][3][4][5][6][7][8]. Collagen fibrils consist of high-aspect-ratio polypeptides, tropocollagen molecules, with a length of ≈300 nm and a diameter of about 1.5 nm, which are laterally staggered.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be possible that the local orientation of collagen monomers or fibrils produced by a cell could help determine the orientation of larger collagen fibers that form by aggregation of those smaller subunits, influencing collagen orientation over distances of hundreds of microns. Thus, although we did not think that enough is known about the control of orientation during fibrillogenesis to explicitly include these effects in our model, our results suggest that the role of fibrillogenesis in controlling collagen fiber alignment and heterogeneity warrants further study and modeling (e.g., (29)(30)(31)(32)). …”
Section: Mechanisms For Generating Heterogeneity: Aligned Deposition mentioning
confidence: 90%